Broadband and entrepreneurship: An empirical assessment of the connection between broadband availability and new business activity across the United States. (November 2022) - Stephens, Heather M.; Mack, Elizabeth A.; Mann, John
Highlights: Investigate the connection between broadband and new business activity. Instrumental variables approach based on development of the Internet by the U.S. military. Broadband availability was associated with an increase in new business activity. Broadband was associated net creation of new businesses. Broadband may have crowded out business activity in the manufacturing industry. Abstract: Research investigating the linkages between broadband and new business activity in countries around the world produce mixed results related to important nuances in this relationship pertaining to industry characteristics, geography, and the skill level of the workforce. Given these nuances, the goal of this study is to investigate the connection between broadband availability and new business activity, building on regional and rural-focused studies within the United States. Specifically, our paper conducts a nationwide assessment of the relationship between broadband and new business activity, in the early years of broadband in the late 1990s/early 2000s when it had the most potential to disrupt industries and open up new entrepreneurial opportunities. Using an instrumental variables approach based on the development of the Internet by the U.S. military, we estimate the impact of broadband availability on total and net new business creation. Results suggest that access to broadband was associated with an increase in new business activity and net creation of new businesses. We also find evidence that access to broadband was important in the creation of businesses in knowledge- oriented industries who benefited from the rise of the Internet. At the same time, we also find broadband may have crowded out business activity in the manufacturing industry. Combined, our results suggest disruptive innovations related to broadband Internet connections are important for small business creation in many, but not all industries. Given these linkages, expanding access to broadband may help generate new business activity and business growth.